Nitrogen and metals as multiple stressors affecting the auto-remediation role of salt marshes : consequences to the ecosystem services - Sousa, Ana (2011)
Tese de doutoramento, Biologia (Ecologia), Universidade de Lisboa, Faculdade de Ciências, 2010